Mujeres y Política en Chile, siglos XIX y XX - Gálvez, Ana; Loyola, Manuel; Álvarez, Rolando (Ariadna Ediciones, 2019)
Chapters of history of Chilean women, 19th and 20th centuries. His social and political performance at different times in the country's history